Sum of Half Factorials!

Calculus Level 4

1 ( 1 2 ) ! + 1 ( 3 2 ) ! + 1 ( 5 2 ) ! + 1 ( 7 2 ) ! + = ? \large\frac{1}{\left(\frac{1}{2}\right)!}+\frac{1}{\left(\frac{3}{2}\right)!}+\frac{1}{\left(\frac{5}{2}\right)!}+\frac{1}{\left(\frac{7}{2}\right)!}+\cdots=\ ?


The answer is 2.29.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

We know that the gamma function Γ ( 1 + x ) = x Γ x = x ! \Gamma (1+x) = x\Gamma {x} = x! and Γ ( 1 2 ) = π \Gamma (\frac{1}{2}) = \sqrt{\pi} . Therefore, the sum:

S = 1 ( 1 2 ) ! + 1 ( 3 2 ) ! + 1 ( 5 2 ) ! + 1 ( 7 2 ) ! + . . . = 1 Γ ( 3 2 ) + 1 Γ ( 5 2 ) + 1 Γ ( 7 2 ) + 1 Γ ( 9 2 ) + . . . = 1 1 2 Γ ( 1 2 ) + 1 3 2 Γ ( 3 2 ) + 1 5 2 Γ ( 5 2 ) + 1 7 2 Γ ( 7 2 ) + . . . = 1 1 2 Γ ( 1 2 ) + 1 3 2 ˙ 1 2 Γ ( 1 2 ) + 1 5 2 ˙ 3 2 ˙ 1 2 Γ ( 1 2 ) + 1 7 2 ˙ 5 2 ˙ 3 2 ˙ 1 2 Γ ( 1 2 ) + . . . = 1 π ( 2 1 + 2 2 1 ˙ 3 + 2 3 1 ˙ 3 ˙ 5 + 2 4 1 ˙ 3 ˙ 5 ˙ 7 + . . . ) = 1 π n = 0 2 2 n + 1 ( 2 n + 1 ) ! ! \begin{aligned} S & = \frac{1}{(\frac{1}{2})!} + \frac{1}{(\frac{3}{2})!} + \frac{1}{(\frac{5}{2})!} + \frac{1}{(\frac{7}{2})!} + ... \\ & = \frac {1} {\Gamma (\frac{3}{2})} + \frac {1} {\Gamma (\frac{5}{2})} + \frac {1} {\Gamma (\frac{7}{2})} + \frac {1} {\Gamma (\frac{9}{2})} + ... \\ & = \frac {1} {\frac{1}{2} \Gamma (\frac{1}{2})} + \frac {1} {\frac{3}{2} \Gamma (\frac{3}{2})} + \frac {1} {\frac{5}{2} \Gamma (\frac{5}{2})} + \frac {1} {\frac{7}{2} \Gamma (\frac{7}{2})} + ... \\ & = \frac {1} {\frac{1}{2} \Gamma (\frac{1}{2})} + \frac {1} {\frac{3}{2} \dot{} \frac{1}{2} \Gamma (\frac{1}{2})} + \frac {1} {\frac{5}{2} \dot{} \frac{3}{2} \dot{} \frac{1}{2} \Gamma (\frac{1}{2})} + \frac {1} {\frac{7}{2} \dot{} \frac{5}{2} \dot{} \frac{3}{2} \dot{} \frac{1}{2} \Gamma (\frac{1}{2})} +... \\ & = \frac{1}{\sqrt{\pi}} \left( \frac{2}{1} + \frac{2^2}{1\dot{}3} + \frac{2^3}{1\dot{}3\dot{}5} + \frac{2^4}{1\dot{}3\dot{}5\dot{}7} +... \right) \\ & = \frac{1}{\sqrt{\pi}} \sum_{n=0}^\infty {\frac{2^{2n+1}}{(2n+1)!!}} \end{aligned}

We know that:

e r f ( x ) = e x 2 π n = 0 ( 2 x ) 2 n + 1 ( 2 n + 1 ) ! ! S = e e r f ( 1 ) = 2.7182 × 0.8427 = 2.29 \begin{aligned} erf (x) & = \frac{e^{-x^2}}{\sqrt{\pi}} \sum_{n=0}^\infty {\frac{(2x)^{2n+1}}{(2n+1)!!}} \\ \Rightarrow S & = e \space erf(1) \\ & = 2.7182 \times 0.8427 = \boxed{2.29} \end{aligned}

Moderator note:

Having a good command / familiarity with various types of function expansions can make it easier to manipulate such infinite sums.

Sometimes, it just boils down to knowing what to substitute in.

Just one doubt how u took 2 2 n + 1 2^{2n+1} .it doesn't seems to include even powers

Kyle Finch - 6 years ago

Log in to reply

You are right. There was an error in my reference Erf -- from Wolfram MathWorld .

Chew-Seong Cheong - 6 years ago

Log in to reply

SO is the problem incorrect or it should be modified to 1 1 2 ! + 2 3 2 ! + 4 5 2 ! + 8 7 2 ! + . . \frac{1}{\frac{1}{2}!}+\frac{2}{\frac{3}{2}!}+\frac{4}{\frac{5}{2}!}+\frac{8}{\frac{7}{2}!}+.. .

now ur method seems to be correct

Kyle Finch - 6 years ago

Log in to reply

@Kyle Finch The problem is correct. The summation equation given my reference was wrong. See image . Note the the expanded series matches = 1 π ( 2 1 + 2 2 1 ˙ 3 + 2 3 1 ˙ 3 ˙ 5 + 2 4 1 ˙ 3 ˙ 5 ˙ 7 + . . . ) = \frac{1}{\sqrt{\pi}} \left( \frac{2}{1} + \frac{2^2}{1\dot{}3} + \frac{2^3}{1\dot{}3\dot{}5} + \frac{2^4}{1\dot{}3\dot{}5\dot{}7} +... \right) .

Chew-Seong Cheong - 6 years ago

Oh really? There is such a series defined for erf(x) \text{erf(x)} ? I 'wasted' my energy computing it(of course using Beta function). But still computing it oneself is nice, made this problem harder.

Kartik Sharma - 6 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...